Trabalho docente (re)velado no dizer do professor de ensino fundamental - Pinto, Adriana Cintra de Carvalho (2009)
Considering the main thesis stood on by the Discursive Social Interactionism, that is, all the texts are the instrument through which the human being transmit interpretations and evaluations relative to the characteristics of his acting that may contribute to the clarity and transformation of this behaving and the Clinic of the Activity thesis that the worker´s voice can bring important meanings of his activities, this research is bound up with the Analysis of Languages, Educational Work and its Relations Group researches, ALTER/CNPq, headquartered at the Postgraduate Study Program in Applied Linguistics from the Pontifícia Universidade Católica de São Paulo (LAEL-PUC/SP) coordinated by The Teacher Doctor Anna Rachel Machado. In this context we had the objective to investigate the interpretations and evaluations of the teaching work reconfigured in texts produced by a Fundamental Course teacher from a public school in Tremembé-SP, with the purpose of knowing better what and how he does or doesn´t to continuously become a teacher. Based on Boutet`s (1995), Clot´s (1999/2006;2001) and Bronckart´s (2008) works, we have used the lookalike´s instruction procedures, developed in the Activity Clinic field through which we have induced the teacher to produce texts (an oral and a written one) in a research status, thematising the teaching activity. The teacher´s texts analyses were made from some text analysis procedures adopted by ALTER/CNPq Group (MACHADO and BROCKART, 2009). Supported by their results we defend the thesis that it is possible to adequate the texts analysis procedure already proposed by ALTER/CNPq Group to the texts analysis produced in the application of the instruction method to the lookalike and that way to develop an adequate and effective research in the Applied Linguistics showing the teaching work characteristics as they really are rebuilt in the texts. As a final conclusion, we share our reflection about the role of researches like that in the transformation of the teacher´s actual work condition.